Gains from trade due to within-firm productivity: Does services exporting matter? - N. Nergiz Dincer; Ayca Tekin-Koru (Kiel Institute for the World Economy (IfW), 2017)
This paper focuses on gains from trade due to rising within-firm productivity in presence of services exporting. The complementarity between exporting and investing in productivity enhancements is investigated by using descriptive regressions using rich, firm-level data for the period 2003-2011 for Turkey. The authors use three productivity measures for robustness purposes. The results show that firms that export both goods and services throughout the sample have higher productivity compared to all other firms in the sample. Another important result of the paper is related to the firms that switch from being goods exporters to goods and services exporters, which exhibit higher productivity than firms that export only goods or firms that switch from services exporting to exporting both goods and services. Finally, within-firm gains from trade as measured by the productivity growth of firms is insensitive to the services exporting status. More importantly, the authors observe no effect of any of export status of firms considered in this paper on their productivity growth.
Keywords: F10; F14; 330; services trade; productivity; exporting status